Philosophy in a feminist voice : critiques and reconstructions - Kourany, Janet A. (Princeton University Press, 1998)
In this book, Janet Kourany offers an antidote to the pervasive and pernicious strains in Western philosophy that discount women. Most areas of Western philosophy tend not only to ignore women, but also to perpetuate long-standing antifeminine biases of the society as a whole. It does not have to be this way. Rather than be part of the problem, philosophy can be a powerful force for much needed social change. In this collection of essays by some of the most noted feminist philosophers, Kourany showcases ideas on the newest work of Western philosophy that is benefiting women as well as men. Inc.